Expression of fungal infection response genes and protein frofiles in oil palm (elaeis guineensis jacq.) roots during basal stem rot infection by ganoderma boninense / Jameel Rabee al-Obaidi - al-Obaidi, Jameel Rabee (2013)
Basal stem rot disease (BSR) is a common disease that affects the Malaysian oil palm. The disease devastates thousands of hectares of oil palm plantings in Southeast Asia every year. It is caused by the fungus Ganoderma boninense, which infects the oil palm trees, causing loss of yield and finally killing the trees. In the present study, gene expression and proteomic investigations were carried out on the root tissues of the oil palm infected with G. boninense. While the gene expression data obtained from this study may be used in future work on the development of resistant or tolerant oil palm varieties against this fatal infection, the proteomics data can be used to develop protein biomarkers that may be used for the early detection of the fungal infection. Three different plant genes related to response to fungal infection, comprising those that express polygalacturonase-inhibiting protein (PGIP), lipid transfer protein (LTP) and pathogen related protein 10 (PR10), were identified in the oil palm, based on conserved sequences of the same genes of other monocots. The three identified gene sequences demonstrated high similarities with their counterparts from the other monocots and up to 100% identity with those of rice. When expression of the genes was studied in the oil palm roots, the highest levels of expression for all three genes were detected in uninfected palms for all the three genes. The levels of expression of the genes significantly decreased subsequent to an infection with G. boninense for all treatment timeframes studied (2, 4, 6 and 8 weeks post infection). Collectively, the gene expression investigation that was performed in this study demonstrated the coordinated down-regulated expression of defence related genes PGIP, LTP and PR10 in the oil palm roots during the early stages of infection with G. boninense. This differential expression may provide some indication as to how the fungus actively suppresses the host response and/or escape being recognized by the host system allowing for the establishment of the infection. In an attempt to identify proteins that may be used as biomarkers for the early detection of G. boninense infection of the oil palm, a proteomics study was performed on proteins extracted from the infected and non-infected root tissues of the oil palm plant. The study allowed for the investigation of the global response of the oil palm genome to the pathogen during the early stages of infection. When profiled by 2-dimensional gel electrophoresis, 61 protein spots were initially detected to be differentially expressed between the uninfected control and infected root tissues. Among the differentially expressed proteins, 22 spots that showed highest differential expression were chosen for identification. This included 13 proteins that were significantly downregulated and 9 that were significantly up-regulated subsequent to the G. boninense inoculation. Analysis by mass spectrometry and database search generated 21 protein hits, with 11 of them considered putatively identified on the basis of MASCOT scores of more than 55. However, among these 11 proteins, two were of unknown functions, while the remainder included enolase, fructokinase, caffeoyl-CoA O-methyltransferase, caffeic acid O-methyltransferase, aminopeptidase, enoyl-acyl carrier protein reductase, pyridoxal 5-phosphate (PLP)-dependent enzyme, malate dehydrogenase and ATP synthase. While the altered expression of these proteins may have some physiological relevance to the plant, such as the need to change its metabolism or being involved in its defence mechanism, these proteins may also be exploited for their potential use as biomarkers for oil palm root infection. The analysis of activation and synthesis of infection/stress related proteins identified can potentially generate a set of biomarkers to discriminate between different defence-related strategies, as diagnostic tools and in the prognosis monitoring of basal stem rot infection.